The photodissociation dynamics of NO2 at 308 nm and of NO2 and N2O4 at 226 nm. - Brouard, M; Cireasa, R; Clark, A; Preston, T; Vallance, C (2006)
Velocity-map ion imaging has been applied to the photodissociation of NO(2) via the first absorption band at 308 nm using (2 + 1) resonantly enhanced multiphoton ionization detection of the atomic O((3)P(J)) products. The resulting ion images have been analyzed to provide information about the speed distribution of the O((3)P(J)) products, the translational anisotropy, and the electronic angular momentum alignment. The atomic speed distributions were used to provide information about the internal quantum-state distribution in the NO coproducts. The data were found to be consistent with an inverted NO vibrational quantum-state distribution, and thereby point to a dynamical, as opposed to a statistical dissociation mechanism subsequent to photodissociation at 308 nm. Surprisingly, at this wavelength the O-atom electronic angular momentum alignment was found to be small. Probe-only ion images obtained under a variety of molecular-beam backing-pressure conditions, and corresponding to O atoms generated in the photodissociation of either the monomer, NO(2), or the dimer, N(2)O(4), at 226 nm, are also reported. For the monomer, where 226 nm corresponds to excitation into the second absorption band, the kinetic-energy release distributions are also found to indicate a strong population inversion in the NO cofragment, and are shown to be remarkably similar to those previously observed in the wavelength range of 193-248 nm. Mechanistic implications of this result are discussed. At 226 nm it has also been possible to observe directly O atoms from the photodissociation of the dimer. The O-atom velocity distribution has been analyzed to provide information about its production mechanism.